1998
DOI: 10.1079/096582198388274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breakfast fat content on glucose tolerance and risk factors of atherosclerosis and thrombosis

Abstract: Twenty-four middle-aged healthy men were given a low-fat high-carbohydrate (5 . 5 g fat; L), or a moderately-fatty, (25 . 7 g fat; M) breakfast of similar energy contents for 28 d. Other meals were under less control. An oral glucose tolerance test (OGTT) was given at 09.00 hours on day 1 before treatment allocation and at 13.30 hours on day 29. There were no significant treatment differences in fasting serum values, either on day 1 or at the termination of treatments on day 29. The following was observed on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
2
8
1
Order By: Relevance
“…26 Based on this variability in metabolism, it could be hypothesised that there are physiological windows of time when consumption of certain nutrients may be favoured. Consistent with this, short-term trials have demonstrated that nutrient composition of meals can influence glucose, insulin and triacylglycerol responses, 27, 28 with higher responses being observed after a night-time meal compared with a day-time meal. 29 …”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…26 Based on this variability in metabolism, it could be hypothesised that there are physiological windows of time when consumption of certain nutrients may be favoured. Consistent with this, short-term trials have demonstrated that nutrient composition of meals can influence glucose, insulin and triacylglycerol responses, 27, 28 with higher responses being observed after a night-time meal compared with a day-time meal. 29 …”
Section: Introductionsupporting
confidence: 56%
“…37 In a series of randomised controlled trials, Frape et al 27 found that small differences in the fat composition of breakfast produce profound effects on diurnal levels of circulating non-esterified fatty acids, which can adversely affect glucose tolerance up to 6 h. 28 Frape et al also demonstrated that subjects given a fatty breakfast followed by a fatty lunch produce larger postprandial glucose responses than individuals given a carbohydrate-rich breakfast followed by a fatty lunch. 27, 28 Together, the above findings may explain why in our study increasing energy intake from carbohydrate in the morning at the expense of fat was associated with lower development of metabolic syndrome and abdominal obesity. The combined evidence also supports the concept that there are physiological windows of time when the human body favours the consumption of some nutrients but not others, with the ends of the day having the greatest influence.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the feeding regimen eliciting the greatest reduction in NEFA concentration (i.e., meal feeding) would result in the lowest amount of these fatty acids being used for VLDL-TAG synthesis. This hypothesis was based on studies demonstrating a greater insulin response and R a NEFA suppression after consumption of increased carbohydrate loads (25)(26)(27). In the present study, no significant difference in concentration of NEFAs, absolute NEFA 16:0 (AUC), or percent VLDL-TAG from NEFAs was found between the two feeding regimens, even though the meal-feeding insulin concentration was significantly greater.…”
Section: Discussioncontrasting
confidence: 39%
“…postprandial S I after breakfast. It is accepted that a fatty breakfast has deleterious effects on glucose tolerance and S I to a lunch-time meal, presumably through effects on NEFA concentrations (Frape et al 1998). In the present study we were able to clarify the effects of breakfast fatty acid composition on these parameters.…”
Section: Discussionmentioning
confidence: 56%